Mathematical model of prevention of terrorist emergencies by detecting masked fire and armored vehicles with radiation devices from aircraft - Divizinyuk , Mykhailo; Lutsenko , Yuri; Myroshnyk, Oleh; Avramenko, Alexander; Bass, Oleg (Social Development and Security, 2020)
The work is devoted to solving an important scientific problem in the field of civil protection, which is to prevent terrorist emergencies by detecting masked fire and armored vehicles with radiation devices used on aircraft. On the basis of experiments conducted in the Chornobyl zone, areas of anomalous zones and shielding parameters of vehicles were determined. The characteristics of aircraft, digital information processing and transmission systems are analyzed and the organization of the search engine is investigated. Models for detecting the range of masked fire and armored vehicles and the probability of detecting a masked vehicle by one or a group of aircraft have been developed. Based on the obtained results, a mathematical model for the prevention of terrorist emergencies was developed.